1997
DOI: 10.1097/00001756-199703240-00035
|View full text |Cite
|
Sign up to set email alerts
|

The apolipoprotein E ε4 allele is not associated with early onset temporal lobe epilepsy

Abstract: A polymorphism of the apolipoprotein E gene, in particular the epsilon 4 allele (ApoE4), has been associated with impaired neuronal phospholipid metabolism and synapse reorganization and has been implicated in several neurodegenerative disorders. Since selective neuronal cell lose and aberrant axonal reorganization represent hall-marks of Ammon's horn sclerosis (AHS) in patients with chronic temporal lobe epilepsy (TLE), the ApoE polymorphism was studied in 125 patients with TLE. The genotype analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 7 publications
1
23
0
1
Order By: Relevance
“…These same molecules would be predicted to protect against DNA fragmentation in TLE patients carrying the APOE ε3 allele. The basic science mechanisms linking APOE ε4 with a reduction in various biomarkers of resilience may, at least in part, underlie the clinical association of the APOE ε4 allele with one or more of the negative outcome factors when human TLE is linked to APOE ε4 , such as increased tendency toward earlier age at onset of TLE and/or bilaterality of hippocampal damage, although not all of these negative TLE/ APOE ε4 associations have been independently confirmed [7-19]. IL-1α is also genetically linked to the risk for developing TLE in at least two independent studies [20].…”
Section: Introductionmentioning
confidence: 99%
“…These same molecules would be predicted to protect against DNA fragmentation in TLE patients carrying the APOE ε3 allele. The basic science mechanisms linking APOE ε4 with a reduction in various biomarkers of resilience may, at least in part, underlie the clinical association of the APOE ε4 allele with one or more of the negative outcome factors when human TLE is linked to APOE ε4 , such as increased tendency toward earlier age at onset of TLE and/or bilaterality of hippocampal damage, although not all of these negative TLE/ APOE ε4 associations have been independently confirmed [7-19]. IL-1α is also genetically linked to the risk for developing TLE in at least two independent studies [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the majority of patients had an early childhood lesion, these fi ndings suggest that ApoE e4 allele may have an important eff ect on determining the length of the silent interval. In contrast to this, there was no difference in the age at onset of epilepsy in patients with focal seizures with copy of the e2, e3 or e4 allele in studies by Kilpatric et al 18 and Blumke et al 19 . Th e same result has been reported by Yeni et al 20 in a group of patients suff ering from mesial temporal lobe epilepsy-hippocampal sclerosis, and by Kauff man et al 21 .…”
Section: Discussionmentioning
confidence: 63%
“…ApoE ε4 genotype is associated with an earlier onset of chronic TLE 17 , but some other studies were not able to fi nd a link between TLE, onset of disease and ApoE polymorphism [18][19][20] . Th e aim of this study was to evaluate the association between ApoE polymorphism and age at onset in patients with non-lesional TLE.…”
Section: Introductionmentioning
confidence: 96%
“…The attempt by Giray et al [24] to further define different genetic predispositions between simple and complex febrile seizures is also difficult to justify given the small number of subjects with complex seizures comprised in their study (n = 17). Other studies have failed to find a causal relationship between ApoE polymorphism and epilepsy: Blumcke et al [25] failed to demonstrate an association between ApoE polymorphism and early onset temporal lobe epilepsy; Yeni et al failed to demonstrate an association between ApoE polymorphism and mesial temporal lobe epilepsy with hippocampal sclerosis; Fu et al [28] reported that ApoE4 does not increase the risk for temporal lobe epilepsy in the Chinese Han population, in the absence of prior trauma. In contrast, Kauffman et al [29] reported that the ApoE4 allele might be associated with an earlier onset of temporal lobe epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, increased glutamate concentration in the synaptic cleft might induce prolonged depolarization with repetitive spiking in neurons leading to seizures. Interestingly, previous studies have considered the potential link between ApoE and seizures, with some studies specifically interested in febrile seizures focusing their analyses on ApoE4 [24], the allele known to be a risk factor for Alzheimer's disease, and other studies considering all three ApoE alleles included other seizure phenotypes [25,26]. However, none of the previous studies was adequately designed to test the hypothesis that ApoE2 might confer a specific predisposition to febrile seizures.…”
Section: Introductionmentioning
confidence: 99%